Numerical Simulation of the Effect of Pulmonary Vascular Resistance on the Hemodynamics of Reoperation After Failure of One and a Half Ventricle Repair - Fu, Yan; Qiao, Aike; Yang, Yao; Fan, Xiangming (Frontiers in Physiology, 2020)
Objective Clinically, one and a half ventricle repair (1.5VR) can cause some fatal complication and reoperation in urgent need. The efficacy of reoperation would be affected by pulmonary vascular resistance (PVR). This essay aims to explore the hemodynamic effects of different pulmonary vascular resistance (PVR) on reoperation after 1.5VR failure. Method The lumped parameter model (LPM) was used to simulate three kinds of reoperations: return biventricular repair (2VR), ligation of azygos vein (1.5VR') and return single ventricular repair (1.0VR), with the value of PVR changing from 1 to 4 times while the other parameters remaining unchanged. Hemodynamics factors, such as the left and right ventricular work and their sum (Plv, Prv, Ptotal), left and right ventricular ejection fraction (LVEF, RVEF), the mean pressure and flow-rate ratio of superior and inferior vena cava respectively (mPsvc\mPivc and mQsvc\mQivc) were analyzed. Results At 1 times of PVR, Plv, Prv, Ptotal, LVEF and RVEF of 2VR are all the highest, followed by 1.5VR' and 1.0VR. The mean cardiac output (mCO) decreased from 91 mL/s to 57.13 mL/s. mPsvc\mPivc and mQsvc\mQivc of 1.5VR' is 3.76, 0.55 respectively. mPsvc\mPivc, mQsvc\mQivc of 2VR and 1.5VR' are 1 and 0.67 respectively. Plv, Prv, Ptotal, LVEF, RVEF and their change rate gradually decreased with the change of PVR from 1 to 4 times. mCO of 2VR, 1.5VR' and 1.0VR decreased by 18.53%, 37.58% and 48.07% respectively. The peak value of the tricuspid flow-rate (Qti) waveform of 2VR and 1.5VR' changed from "E peak" to "A peak "; mPsvc\mPivc of 1.5VR' increased from 3.76 to 6.77 and mQsvc\mQivc decreased from 0.55 to 0.36, while mPsvc\mPivc, mQsvc\mQivc remained the same for other two surgical procedures. Conclusion The effect of PVR on the change rate of Plv, Prv, Ptotal, LVEF and RVEF were different in three surgical procedures. Comprehensive analysis of EF and mCO indicates that PVR has a greater impact on 1.5VR' and 1.0VR. Therefore, the selection strategy of reoperation should focus on PVR.